Rational Design of Isolated Tetrahedrally Coordinated Ti(IV) Sites in Zeolite Frameworks for Methyl Oleate Epoxidation - Sorasak Klinyod; Krissanapat Yomthong; Ploychanok Iadrat; Pinit Kidkhunthod; Kittisak Choojun; Tawan Sooknoi; Chularat Wattanakit (Chemistry - An Asian Journal, 2024)
. This observation discloses an alternative strategy for optimizing catalyst efficiency in the rational design of the Ti-embedding zeolite catalyst, endeavoring to reach highly efficient catalytic performance.
Keywords: Polyoxometalates: Synthesis and Applications; Zeolite Catalysis and Synthesis; Metal-Organic Frameworks: Synthesis and Applications